KINERJA APARATUR SIPIL NEGARA (ASN) PEMERINTAH KOTA MATARAM - Amiartuti Kusmaningtyas (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2014)
The development of each region will be realized if the perpetrators of the organization working units as the spearhead of the executor in the area feel the peace and comfort in the work. This study aims to determine the Organization Climate Effect on Employee Performance with Organization Commitment and Job Satisfaction as an intervening variable in the City of Mataram. Existing problems related to the low performance of employees. It can be observed from the number of employees who can not complete the task in accordance with a predetermined time. This condition occurs partly because many employees are coming late, doing things that are less productive. The study population was Mataram City Government employees spread over 30 unit organizations with a sample of 150 respondents. Data were analyzed using SEM (Structural Equation Modeling) v.22. and SPSS v.19. The results of the analysis proves, 5 hypothesis has significant influence while one hypothesis has not a significant influence. Significant influence include: Organization Climate on Organization Commitment, Organization Climate on Job Satisfaction, although very small. Organization Commitment on Employee Performance, Job Satisfaction on Employee Performance, Organization Climate on employee performance, while the Organization Commitment on Job Satisfaction has no significant effect.